Escalation and Morphological Constraints of Antagonistic Armaments in Water Striders - Crumière, Antonin Jean Johan; Armisén, David; Vargas-Lowman, Aïdamalia; Kubarakos, Martha; Moreira, Felipe Ferraz Figueiredo; Khila, Abderrahman (Frontiers in Ecology and Evolution, 2019)
Sexual conflict may result in the escalating coevolution of sexually antagonistic traits. However, our understanding of the evolutionary dynamics of antagonistic traits and their role in association with sex-specific escalation remains limited. Here we study sexually antagonistic coevolution in a genus of water striders called Rhagovelia. We identified a set of male grasping traits and female anti-grasping traits used during pre-mating struggles and show that natural variation of these traits is associated with variation in mating performance in the direction expected for antagonistic coevolution. Phylogenetic mapping detected signal of escalation of these sexually antagonistic traits suggesting an ongoing arms race. Moreover, their escalation appears to be influenced by a trade-off with dispersal through flight in both sexes. Altogether our results highlight how sexual interactions and natural selection may have shaped sex-specific antagonistic trait coevolution.